The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1108/dat-05-2018-0023
|View full text |Cite
|
Sign up to set email alerts
|

Consumer participation in drug treatment: a systematic review

Abstract: It is unclear how consumer participation (CP) can be optimised to transform drug and alcohol treatment services and improve health outcomes. This paper presents the findings of a systematic review examining the types and benefits of activities, and the factors that facilitate CP in drug treatment services. Design A structured search of four databases was undertaken to identify peer reviewed primary research literature in English. Screened articles were appraised. A content analysis was applied to examine the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 40 publications
(173 reference statements)
7
38
0
Order By: Relevance
“…Our ndings are consistent with several studies which have shown that experiential workers are not always accepted and respected in the workplace due to their history of substance use [32,33,65,66]. Some studies have also reported that support workers without lived experience of substance use have negative attitudes towards experiential workers, rooted in stereotypes and stigma towards PWUD [31][32][33]65]. These negative attitudes are apparent in the terminology used by support workers to de ne experiential workers, including "unstable," "manipulative," "untrustworthy," and "lacking capacity to participate" [31][32][33]65].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our ndings are consistent with several studies which have shown that experiential workers are not always accepted and respected in the workplace due to their history of substance use [32,33,65,66]. Some studies have also reported that support workers without lived experience of substance use have negative attitudes towards experiential workers, rooted in stereotypes and stigma towards PWUD [31][32][33]65]. These negative attitudes are apparent in the terminology used by support workers to de ne experiential workers, including "unstable," "manipulative," "untrustworthy," and "lacking capacity to participate" [31][32][33]65].…”
Section: Discussionsupporting
confidence: 93%
“…This explains why 40% of the survey participants listed "work situation, including working conditions" as one of their top three stressors. Our ndings are consistent with several studies which have shown that experiential workers are not always accepted and respected in the workplace due to their history of substance use [32,33,65,66]. Some studies have also reported that support workers without lived experience of substance use have negative attitudes towards experiential workers, rooted in stereotypes and stigma towards PWUD [31][32][33]65].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, feeling a part of treatment decisions also strengthened their relationships. These findings have been illuminated elsewhere [55,56,59]. For example, Ness et al [55] found that participant experiences collaborating with practitioners required "not being judged".…”
Section: Discussionmentioning
confidence: 88%